Analisis Ambiguitas Makna yang Terkandung dalam Al-Qur’an Surah Al-Baqarah - Salman Jufri; Elisa Devi Sari; Rizky Fadliyah Nurkhasanah (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2023)
This article explains the ambiguity of meaning contained in the verses of the Qur'an. In the study of semantics, ambiguity or blurring of meaning can be caused by several things, including the general nature of words or sentences (generic), words or sentences are never one hundred percent homogeneous, etc. Well, this is what drives the writer to conduct research on the ambiguity contained in Surah Al-Baqarah. In the article, 5 verses in surah Al-Baqarah are found which contain ambiguity, including verses:187, 220, 223, 228 dan 244. By using direct and indirect quotation methods, the author tries to examine and analyze ambiguity as a characteristic contained in This Al-Qur'an Surah Al-Baqarah, so that the objectives in the verse can be determined and provide understanding for the reader, it is also full of messages and meanings.